TARI RONGGENG BEKEN AS THE CULTURAL IDENTITY OF A MULTICULTURAL COMMUNITY IN PERFORMANCE STUDIES PERSPECTIVE - Ayu, Anjani; Nursilah (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
The Ronggeng Beken dance is a traditional dance art of multicultural communities in Bekasi City. This research aims to analyze the cultural identity of the Ronggeng Beken Dance in a multicultural society from a performance studies perspective. The method used in this research is a qualitative method with an ethnographic approach. Data collection was carried out by observation, interviews and document study. The results of the research explain that the Ronggeng Beken Dance, as a traditional dance art of multicultural society in Bekasi City, is a representation of Bekasi society which reflects the ethnic and cultural diversity in Bekasi City. Apart from that, mass performances of the Ronggeng Beken Dance, when analyzed from a performance studies perspective, produce a cultural identity for the city of Bekasi. Therefore, as a cultural identity, the preservation of the Bekasi Ronggeng Dance should continue to be carried out by the people of Bekasi City, one of which is by utilizing the role of education, both informal and formal education.